Frailty, prefrailty and employment outcomes in Health and Employment After Fifty (HEAF) Study. Issue 7 (6th January 2017) - Palmer, Keith T; D'Angelo, Stefania; Harris, E Clare; Linaker, Cathy; Gale, Catharine R; Evandrou, Maria; Syddall, Holly; van Staa, Tjeerd; Cooper, Cyrus; Aihie Sayer, Avan; Coggon, David; Walker-Bone, Karen
Abstract : Objectives: Demographic changes are requiring people to work longer. No previous studies, however, have focused on whether the 'frailty' phenotype (which predicts adverse events in the elderly) is associated with employment difficulties. To provide information, we assessed associations in the Health and Employment After Fifty Study, a population-based cohort of 50–65-year olds. Methods: Subjects, who were recruited from 24 English general practices, completed a baseline questionnaire on 'prefrailty' and 'frailty' (adapted Fried criteria) and several work outcomes, including health-related job loss (HRJL), prolonged sickness absence (>20 days vs less, past 12 months), having to cut down substantially at work and difficulty coping with work's demands. Associations were assessed using logistic regression and population attributable fractions (PAFs) were calculated. Results: In all, 3.9% of 8095 respondents were classed as 'frail' and 31.6% as 'prefrail'. Three-quarters of the former were not in work, while 60% had left their last job on health grounds (OR for HRJL vs non-frail subjects, 30.0 (95% CI 23.0 to 39.2)). Among those in work, ORs for prolonged sickness absence, cutting down substantially at work and struggling with work's physical demands ranged from 10.7 to 17.2. The PAF for HRJL when any frailty marker was present was 51.8% and that for prolonged sickness absence was 32.5%. Associations were strongest with slow reported walking speed. Several associations were stronger in manual workers than in managers. Conclusions: Fried frailty symptoms are not uncommon in mid-life and are strongly linked with economically important adverse employment outcomes. Frailty could represent an important target for prevention.